Psychosocial and Legal Perspectives of Marital Breakdown With Special Emphasis on Spain - Gaffal, Margit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book provides a comprehensive overview of the psychosocial and legal aspects of divorce with special reference to the situation in Spain, addressing the grounds for divorce and its impact on parents and children. Theoretical approaches are applied that take into account the psychosocial conditions and the Spanish legislation. Subsequenty, an empirical analysis of preferred custody arrangements reveals some of the current problems that are associated with a joint custody regime. Lastly, the suitability of divorce mediation is examined within the framework of the Spanish legislation.
Grounds for Divorce -- Factors Influencing Ex-spouses$1 (BAdjustment to Divorce -- Post-divorce Adjustment of Children and Adolescents -- Characteristics and Problems of Custody Arrangements -- Divorce Mediation.s
Keywords: Law; Civil law; Law -- Psychological aspects; Law; Private International Law, International & Foreign Law, Comparative Law; European Law; Law and Psychology; Sociology, general; Civil Law